Nudging a Pseudo‐Science Towards a Science—The Role of Statistics in a Rainfall Enhancement Trial in Oman. (2nd February 2022) - Chambers, Ray; Beare, Stephen; Peak, Scott; Al‐Kalbani, Mohammed
Summary: Although cloud seeding is a commonly used and plausible method for rainfall enhancement, its practical efficacy has not been established for seeding of convective clouds with hygroscopic materials. Other methods of rainfall enhancement are viewed as much less plausible. Thus, although increased electrical charge has been shown to enhance precipitation in cloud chamber experiments, exactly how ionisation of clouds can increase rainfall in the open atmosphere remains conjectural. A trial of the efficacy of ionisation for rainfall enhancement in the Hajar Mountains of Oman was carried out over 2013–2018. This paper provides some background to this non‐mainstream approach to increasing rainfall, showing how statistical modelling of rainfall data might be used to nudge rainfall enhancement via ionisation towards a more scientifically acceptable status. Analysis of the data collected in the trial shows that ionisation led to a statistically significant enhancement in positive rainfall in gauges located up to 70 km downwind of the ionisers. A headline analysis specified prior to commencement of the trial resulted in an estimate of 16.23% enhancement relative to rainfall that would have fallen without any ionisation, while a more sophisticated after the event analysis increased this estimate to 17.64%.